2017
DOI: 10.1111/phn.12347
|View full text |Cite
|
Sign up to set email alerts
|

e‐Health and new moms: Contextual factors associated with sources of health information

Abstract: Mothers widely used e-Health related media, but use was associated with contextual factors. In public health efforts to reach new mothers, partnering with mother-favored Web sites, focusing on audience-relevant media, and adopting attributes of successful sites are recommended strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…One study did not meet the criteria for considering ethical issues as ethics approval was not mentioned (35). Findings were clearly presented in all but three studies (22, 34, 35). The research value was adequately discussed in most studies, although in three studies (33, 35, 38) there was limited discussion on new areas of research identified and how the findings may apply to other populations.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…One study did not meet the criteria for considering ethical issues as ethics approval was not mentioned (35). Findings were clearly presented in all but three studies (22, 34, 35). The research value was adequately discussed in most studies, although in three studies (33, 35, 38) there was limited discussion on new areas of research identified and how the findings may apply to other populations.…”
Section: Resultsmentioning
confidence: 72%
“…Of the included studies, four were conducted in Australia (3133, 37), three in the USA (3436), one in England (22), and one in Bangladesh (38). Five studies conducted interviews (22, 31, 32, 36, 37), two conducted focus groups (33, 35), one conducted a survey (34), and one conducted a combination of surveys, focus groups, and interviews (38). In all studies, participants were within the first year after birth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actualmente otras plataformas como Youtube o Instagram son utilizadas por mujeres para ilustrar su maternidad, en canales específicos sobre crianza o desde cuentas de temática general, algunas de las cuáles se han profesionalizado, convirtiendo a esas personas anónimas en influencers (6) , ya que congregan a su alrededor a un gran número de seguidores. En este sentido, estudios recientes describen como un 46% de las madres utilizan YouTube para acceder a contenidos vinculados con la maternidad y la crianza (7) . Durante siglos, la información relativa a la maternidad estuvo en manos de profesionales y de instituciones, sin que testimonios directos de mujeres pudieran ser accesibles a grandes audiencias.…”
Section: Introductionunclassified